SAFETY INTEGRITY LEVEL ASSESSMENT AT URANIUM EVAPORATOR AND DEPOSITION VESSEL IN NON NUCLEAR REACTOR INSTALLATIONS - Oktavianto, Putra; Kundari, Anis Noor; Saputra, Ade; Abdurrosyid, Imam; Sholikhah, Munisatun; Saputra, Andri (Urania : Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2023)
The operation of non-reactor nuclear installations that use nuclear material in the process must be ensured safely during the process. One of the assessments of the safety level of the protection system that has been owned by the installation is using the Safety Integrity Level (SIL) which assesses the safety level of the protection system based on the value of the risk reduction factor that the protection system can achieve. The uranium evaporator and deposition vessel at the Experimental Fuel Element Installation (EFEI) is one of the installations that uses nuclear material in the process so it is necessary to assess the SIL of these 2 vessels. The piping and instrumentation diagram (P&ID) is used to determine the SIL value and Safety Instrumented System (SIS) component are installed in evaporator and deposition vessel. Maintenance data and OREDA (Offshore Reliability Data) are used to determine the failure rate. After knowing and determining the installed SIS components, then determining the architecture vote of the Safety Instrumented Function (SIF) based on the P&ID diagram, so that it can be known that the installed SIS uses vote 1oo1, 1oo2, 1oo3, or the appropriate vote. The installed SIF architecture vote will determine the equation used to calculate the Probability Failure on Demand (PFD). The total PFD obtained is adjusted to the SIL table to find out what SIL level the installed protection system is at. The value of the safety level of the protection system with SIL assessment in the evaporator vessel obtained 2 protection systems with SIL values of level 2 all and in the deposition vessel obtained 2 protection systems with SIL values of level 1 and level 2. The SIL value in the evaporator and deposition vessel analyzed has not reached level 3 or 4, so it is necessary to add SIF to the SIS protection system to increase the SIL value until the SIL value is obtained between level 3 or 4 because safety in the operation of non-reactor nuclear installations is absolute.Keywords: Non-Reactor Nuclear Installations, PFD, SIF, SIL, SIS